Biopsychosocial barriers affecting recovery after a minor transport‐related injury: A qualitative study from Victoria. (3rd June 2019) - Samoborec, Stella; Ayton, Darshini; Ruseckaite, Rasa; Evans, Susan M
Abstract: Objective: The aim of the study was to understand the recovery phenomena and to explore participants' perspectives on the biopsychosocial facilitators and barriers affecting their recovery after a minor transport injury. Methods: A qualitative method was used involving semi‐structured interviews with 23 participants who sustained a minor transport injury. Interviews and analysis were guided by the biopsychosocial model (BPS) of health. The outcomes were themes capturing biopsychosocial barriers to, and personal experiences of, recovery using a previously defined framework. Results: The themes indicate that recovery is a multifaceted phenomenon affected by comorbidities such as chronic pain, depression and anxiety. A range of subsequent complexities such as the inability to self‐care and undertaking daily domestic duties, and incapacity to participate in recreational activities were major barriers to recovery. These barriers were found to be an on‐going source of frustration, dissatisfaction and a perceived cause of depressive symptomatology in many participants. Most participants reported mixed feelings of the care received. Other common issues raised included a lack of understanding of the assessment time, regular follow‐up, guidance and on‐going support. Conclusion: This study revealed that recovery after a minor transport‐related injury was a challenging, complex, demanding and a long‐term process for the individuals in this study. Findings from this limited cohort suggested that, for participants to return to their pre‐accident health status, a more coordinated approach to information and care delivery may be required.